2011
DOI: 10.3109/15368378.2011.596250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sinusoidal electromagnetic fields on histopathology and structures of brains of preincubated white leghorn chicken embryos

Abstract: There are several reports indicating linkages between exposures to 50-60 Hz electromagnetic fields and abnormalities in the early stages of chicken embryonic development. Based on our previous published research carried out at the Department of Animal Sciences, Faculty of Biological Sciences, Shahid Beheshti University, effects of sinusoidal electromagnetic fields on histopathology and structures of brains of preincubated white leghorn hen eggs were investigated. Three hundred healthy fresh fertilized eggs (55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Most studies of the association between MFs and embryonic development have been performed in chickens or rats and showed that electromagnetic fields had adverse effects on brain cells, with an increased number of apoptotic cells and degeneration of brain tissues of exposed chick or mice embryos [5], [7], [26], [27]. However, exposure levels in animal research have always been higher than those that human populations are exposed to in daily life [24], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of the association between MFs and embryonic development have been performed in chickens or rats and showed that electromagnetic fields had adverse effects on brain cells, with an increased number of apoptotic cells and degeneration of brain tissues of exposed chick or mice embryos [5], [7], [26], [27]. However, exposure levels in animal research have always been higher than those that human populations are exposed to in daily life [24], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…Both in vivo and in vitro studies have shown associations between MFs and adverse health effects that include increased risk of miscarriage [1][3], lowered sperm quality [4], and up-regulation genes involved in apoptosis [5][7]. However, the biological hazard of MFs remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although minimal or nonsignificant teratogenic effects on the CNS have been reported (Hoyer et al, 2012; Wiley et al, 1992; Yu et al, 1993), it appears that the specific parameters of the applied field (i.e., waveform) may be one of the most important factors to consider in the study of teratogenesis. For instance, sinusoidal or square‐wave pulses can be harmful to CNS growth and development but typically require field strengths on the order of a millitesla or higher to produce reliable effects (Gona et al, 1993; Juutilainen et al, 1986; Lahijani et al, 2011; Sikov et al, 1984; Ubeda et al, 1983). In contrast, we have found that wave‐form patterns whose intrinsic shapes (often asymmetric or irregular pulse patterns) and interstimulus intervals have been designed to simulate common physiological or naturalistic phenomena can also be effective in altering the development of the rat brain even when applied at flux densities several magnitudes lower (<1 μT) (McKay and Persinger, 1999; McKay et al, 2003; St‐Pierre et al, 2008; St‐Pierre and Persinger, 2003, 2008; Whissell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%